Learn from your mistakes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Technical consultation on the development of market information services for small operators in the agricultural sectors of ACP countries. Edited by K Batjes-Sinclair, CTA (working document). 2001. 83 pp. CTA number 8023. 5 credit points